Betta splendens larviculture of using rotifers Brachionus calyciflorus and infusoria as a feed source (Orinoquia, 2016)
In larviculture fish of small mouth, the kind of live food supplied, as well as the most appropriate delivery times and transition between one diet and other are of great importance. The rotifers and infusorious are commonly used as first live feed for Betta splendens larvae, difficult species to feed with inert diets during the first days of life. The present study was aimed to determine the effect of rotifer Brachionus calyciflorus as a source of live feed on the larval rearing of B. splendens. Therefore, a larviculture experiment was organized, in which the transition of rotifers or infusoria to Artemia, under two different time periods, the first was rotifers supply for 3 or 6 days (T1 and T2). The second was Infusoria supply 3 or 6 days (T3 and T4). In each treatment, Artemia was supplied after the period rotifer feed. The parameters of temperature and pH were monitored. Four replicates per treatment, to which the survival and growth in total length were measured. Multiwell plates of 6 well and ten larvae were used per well. Statistical differences between treatments were presented (p 0,05). The larvae fed with rotifer grew more rapidly than infusoria diets, reaching 10,1 ± 0,4, 9,4 ± 0,4, 7,9 ± 1 and 7,4 ± 0,4 mm, for T1, T2, T3, and T4, respectively. Survival was also higher in treatments with rotifers, presenting 90 and 85,5% for T1 and T2, compared with 54,4 and 52,3% for T3 and T4. Rotifers are better food than infusorians for B. splendens larvae, improving larviculture prospects.
Keywords: Live feed; Betta splendens; larviculture; rotifers; Siamese fighting fish